Luminescence and transfer for power characteristics of Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ phosphor for WLEDs - My Hanh Nguyen Thi; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
We apply the high-heat solid-state technique to create a sequence of phosphors Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+. In Sr4La(PO4)3Othe luminescence characteristics, heat resistance, and transfer of energy between Ce3+ and Tb3+ as well as Mn2+ were thoroughly studied. The insertion of the sensitizer Ce3+ ions can significantly flatter the emission of the color green from Tb3+ and the emission of the color red from Mn2+ via energy transfer. By modifying the Ce3+/Tb3+ and Ce3+/Mn2+ ion ratios, it can change the emission color. White light, which has color coordinates of 0.3326, 0.3298, were produced by the Sr4La(PO4)3O: 0.12Ce3+, 0.3Mn2+ 0.12Ce3+, 0.3Mn2+ specimen, showing Sr4La(PO4)3O:Ce3+,Tb3+,Mn2+ might be profitable in white LEDs.